Importation and Circulation of Vaccine-Derived Poliovirus Serotype 2, Senegal, 2020–2021 - Martin Faye; Ousmane Kébé; Boly Diop; NDack Ndiaye; Annick Dosseh; Abdoulaye Sam; Aliou Diallo; Hamet Dia; Jean Pierre Diallo; Ndongo Dia; Davy Evrard Kiori; Ousmane Madiagne Diop; et al. (Emerging Infectious Diseases, 2022)
Environmental surveillance for poliovirus is increasingly used in poliovirus eradication efforts as a supplement to acute flaccid paralysis (AFP) surveillance. Environmental surveillance was officially established in 2017 in Senegal, where no poliovirus had been detected since 2010. We tested sewage samples from 2 sites in Dakar monthly for polioviruses. We identified a vaccine-derived poliovirus serotype 2 on January 19, 2021, from a sample collected on December 24, 2020; by December 31, 2021, we had detected 70 vaccine-derived poliovirus serotype 2 isolates circulating in 7 of 14 regions in Senegal. Sources included 18 AFP cases, 20 direct contacts, 17 contacts in the community, and 15 sewage samples. Phylogenetic analysis revealed the circulation of 2 clusters and provided evidence on the virus introduction from Guinea. Because novel oral polio vaccine serotype 2 was used for response activities throughout Senegal, we recommend expanding environmental surveillance into other regions.